ANALYSIS OF TYPES OF ENGLISH PHRASAL VERBS ACCORDING TO THE STRUCTURE - Khamidov, Tohirjon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Phrasal verbs have very high utility factor in English speaking especially. They fall under the wider category of most verbs which is referred to as multi-word verbs. These types of verbs and the other terms of multiword verbs are very crucial in the system of English language. A very large number of verbs , that fall under the class of multi-word verbs, that is, phrasal verbs are used commonly in day to day conversation. A phrasal verb is a common manned term that describes verb combinations, such as “pick up,” “turn on,” or “get on with”. For convenience, many people refer to all multi-word verbs as phrasal verbs. Such sentences contain two components: a simple verb and other parts of speech. Adding to the verb, other words can include prepositions and adverbs. Such verbs usually have a few word combinations sending a single meaning which is why such expression are often called as ‘phrasal verbs’. The concept that needs to be emphasized, however, is that these expressions are still considered headwords. The term ‘get’ is a verb. The term ‘get up is also a verb; it is a different kind of action word. The terms ‘get’ and ‘get up’ refer to different verbs. The two verbs mean complete opposite things.